B-Cell Chronic Lymphocytic Leukemia with 11q22.3 Rearrangement in Patient with Chronic Myeloid Leukemia Treated with Imatinib - Krzysztof Lewandowski; Michał Gniot; Maria Lewandowska; Anna Wache; Błażej Ratajczak; Anna Czyż; Małgorzata Jarmuż-Szymczak; Mieczysław Komarnicki (Case Reports in Medicine)
The coexistence of two diseases chronic myeloid leukemia (CML) and B-cell chronic lymphocytic leukemia (B-CLL) is a rare phenomenon. Both neoplastic disorders have several common epidemiological denominators (they occur more often in men over 50 years of age) but different origin and long term prognosis. In this paper we described the clinical and pathological findings in patient with CML in major molecular response who developed B-CLL with 11q22.3 rearrangement and Coombs positive hemolytic anemia during the imatinib treatment. Due to the presence of the symptoms of autoimmune hemolytic anemia and optimal CML response to the imatinib treatment, the decision about combined therapy with prednisone and imatinib was made. During the follow-up, the normalization of complete blood count and resolution of peripheral lymphadenopathy were noted. The hematologic response of B-CLL was diagnosed. The repeated FISH analysis of cultured peripheral blood lymphocytes showed 2% of cells carrying 11q22.3 rearrangement. At the same time, molecular monitoring confirmed the deep molecular response of CML. The effectiveness of such combination in the described case raises the question about the best therapeutic option in such situation, especially in patients with good imatinib tolerance and optimal response.